Regulatory considerations for study of infant protection through maternal immunization. Issue 26 (9th June 2022) - Mutanga, Jane Namangolwa; Whitaker, Barbee I.; Forshee, Richard A.
Abstract: Childhood Immunization is one of the critical strategies to decrease infant morbidity and mortality due to infectious diseases, but primary immunization schedules for infants in most countries start at 2 months of age. Childhood vaccines therefore begin providing adequate protection later in life, leaving infants vulnerable to infectious diseases and creating an immunity gap that results in higher morbidity and mortality among younger infants. Maternal immunization, the practice of vaccinating individuals during pregnancy, reduces the risk of infant infection primarily through the transfer of protective maternal antibodies to the fetus during late pregnancy. Although much progress has been made in public health policies to support maternal immunization research, inclusion of pregnant individuals and children in clinical trials remains challenging. This has resulted in paucity of evidence regarding safety and effectiveness of vaccines to support licensure of products intended for use during pregnancy and lactation to prevent disease in the infant. In addition, although safeguards for clinical research in pregnancy are supportive, experimental vaccines, e.g., Respiratory Syncytial Viru s, are more complicated to study because data on safety, efficacy, and dosing are limited. This requires randomized controlled trials with safety monitoring for the mother, the fetus, and the infant with follow-up for at least 1 year or longer to assess long-term health outcomes that may be associated with peripartum vaccine exposure. The goal of this paper is to discuss the general regulatory considerations for clinical research to evaluate safety and effectiveness of vaccines administered during pregnancy to protect infants from disease. This could be useful to inform future vaccine trials. This discussion is not intended to provide agency guidance nor to articulate agency policy.